The Effectiveness Of Toothbrushing Using Chlorhexidine Gluconate 0.2% On Ventilator Associated Pneumonia (Vap) - Ridho Kunto Prabowo; Novi Dwi Irmawati (Poltekkes Kemenkes Semarang, 2022)
Background: Ventilator-Associated Pneumonia (VAP) can cause the patient's length of stay in the ICU to be prolonged and can cause infection so that if not treated, it can cause sepsis in patients who can eventually lead to death. Toothbrushing with the right frequency for patients, namely toothbrushing using 0.2% Chlorhexidine Gluconate liquid 2 times a day or 3 times a day, especially for intubated individuals, is essential to prevent the occurrence of Ventilator-Associated Pneumonia. The purpose of this study was to determine the difference in the effectiveness of toothbrushing using 0.2% chlorhexidine gluconate, three times a day and twice a day on the incidence of Ventilator-Associated Pneumonia. Methods: This study is quantitative research with a descriptive approach with a quasi-experimental method with a post-test only non-equivalent control group design. The sampling technique used purposive sampling, with a total sample of 16 patients who were toothbrushed twice a day and 16 patients who were toothbrushed 3 times a day. The instrument used to assess VAP incidence was an observation sheet consisting of a Clinical Pulmonary Infection Score measurement result sheet. Results: The results showed that the effectiveness of tooth brushing using chlorhexidine gluconate 0.2% with a frequency of 2 times a day was 81.3%, and a frequency of 3 times a day was 75%. Data analysis using chi-square showed p-value = 0.500. Conclusion: there is no difference between the effectiveness of toothbrushing using 0.2% chlorhexidine gluconate with a frequency of 2 times a day or 3 times a day. It is recommended that ICU nurses perform toothbrushing using 0.2% chlorhexidine gluconate fluid routinely, either 2 times a day or 3 times a day in patients on a ventilator.